2014
DOI: 10.1093/deafed/enu022
|View full text |Cite
|
Sign up to set email alerts
|

Foundations for Literacy: An Early Literacy Intervention for Deaf and Hard-of-Hearing Children

Abstract: The present study evaluated the efficacy of a new preschool early literacy intervention created specifically for deaf and hard-of-hearing (DHH) children with functional hearing. Teachers implemented Foundations for Literacy with 25 DHH children in 2 schools (intervention group). One school used only spoken language, and the other used sign with and without spoken language. A “business as usual” comparison group included 33 DHH children who were matched on key characteristics with the intervention children but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 45 publications
4
43
0
2
Order By: Relevance
“…These assertions clearly align with the premise of the SVR. In fact, several research teams have explicitly referenced the SVR or similar cognitive models when discussing phonological skills as essential components of both early and conventional reading for deaf learners (e.g., [38][39][40]). The alternative view, in which phonological skills are not considered a necessary element (e.g., [37]), has been critiqued because it has not been contextualized within an extant model of reading, and an alternative hypothesis of development has not been empirically demonstrated [3].…”
Section: Historical Research Evidence and The Svrmentioning
confidence: 99%
See 2 more Smart Citations
“…These assertions clearly align with the premise of the SVR. In fact, several research teams have explicitly referenced the SVR or similar cognitive models when discussing phonological skills as essential components of both early and conventional reading for deaf learners (e.g., [38][39][40]). The alternative view, in which phonological skills are not considered a necessary element (e.g., [37]), has been critiqued because it has not been contextualized within an extant model of reading, and an alternative hypothesis of development has not been empirically demonstrated [3].…”
Section: Historical Research Evidence and The Svrmentioning
confidence: 99%
“…Even though several scholars in the field have contextualized their intervention research within a conceptual model of development (e.g., [38][39][40]), the findings of the NRP [34] are more frequently referenced as a foundation for this work. This situation may not differ substantially from the field of reading more broadly, as it has been suggested that curricular standards tend to drive instruction more frequently than cognitive models [13].…”
Section: Qualitative Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for the absence of a coherent treatment literature include the diversity of the population of those with hearing impairment (e.g., Ertmer, Leonard, & Pachuilo, 2002; as well as the diversity of the goals addressed by different treatment methods (White & BrennanJones, 2014). For example, some of the more recent studies have targeted diverse areas such as narratives (Justice, Swanson, & Buehler, 2008), literacy (Lederberg, Miller, Easterbrooks, & Connor, 2014), and language development broadly defined (Ertmer et al, 2002;Hogan, Stokes, White, Tyzkiewicz, & Woolgar, 2008). To our knowledge, there has not been a treatment procedure that specifically targets morphology in the oral domain for children with cochlear implants.…”
Section: Discussionmentioning
confidence: 99%
“…Letter sounds are often considered a print awareness measure (Ambrose et al, 2012;Webb et al, 2015), and its loading onto both factors could indicate that children are using the visual information available in print to help them learn sound segments (Easterbrooks et al, 2008;Dillon et al, 2012). Consistent with this hypothesis, in school-age readers who use CIs, those programs that use print materials as part of the phonological awareness trainingsuch as by teaching sound-letter correspondence-show growth on general phonological awareness skills (Lederberg et al, 2014), providing evidence that an approach that builds on children's existing strengths may lead to greater literacy success. We do not claim that auditory access plays no role in phonological sensitivity development for preschoolers who use CIs, rather, we argue that print information can help children resolve their poor spectral resolution to learn speech segments.…”
Section: Co-development Of Print Awareness and Phonological Sensitivitymentioning
confidence: 92%